The Role of Urine-1 and Urinalysis in the Diagnosis of Acute Kidney Injury in Liver Transplantation - Lima, Camila; Brandão, Luciana Severo; Correa , Maria de Fatima; Macedo, Etienne (Brazilian Journal of Transplantation, 2025)
Introduction: Acute kidney injury (AKI) is a common complication in the intensive care unit. Urine-1 (U-1) is a frequently overlooked tool for assessing AKI; moreover, there is no evidence-based consensus on its use. This study aimed to investigate the role of U-1 and urinary microscopy (UM) in diagnosing severe AKI and the need for renal replacement therapy (RRT) in patients undergoing liver transplantation (LT). Methods: Our hypothesis was to determine whether the urinary parameters available in U-1 and UM are associated with the diagnosis of severe AKI and the need for RRT. We evaluated U-1 and UM 6 hours after LTx. The criterion for diagnosing AKI was based on Kidney Disease Improving Global Outcomes (KDIGO) guidelines, relying solely on serum creatinine levels within one week. Results: Eighty-seven patients developed AKI in the first week after LT. The diagnosis of severe AKI (KDIGO 2 and 3) was found in 59 patients. Six hours after LT, the variables in U-1 were predictors of severe AKI, with the area under the curve (AUC) of 0.65 for proteins, 0.68 for leukocytes, and 0.63 for erythrocytes. In determining RRT, these variables performed better with AUC: 0.72 for proteins, 0.69 for leukocytes, and 0.68 for erythrocytes. The non-AKI and AKI groups showed a similar distribution in UM. Conclusion: Simple and commonly used parameters in clinical practice, such as proteinuria, erythrocyturia, and leukocyturia, can be valuable tools for diagnosing severe AKI and the need for RRT.